1995
DOI: 10.1007/bf00010120
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of rhizobia-inoculated wild legumes Argyrolobium flaccidum, Astragalus graveolens, Indigofera gangetica and Lespedeza stenocarpa in providing a vegetational cover in an unreclaimed limestone quarry

Abstract: Several legume-Rhizobium associations were evaluated by sowing and broadcast of seeds encapsulated with polyacrylamide-entrapped rhizobia (PER) in an opencast limestone quarry in the outer ranges of the Himalaya . Four wild legumes, Lespedeza stenocarpa, Astragalus graveolens, Argyrolobium flaccidum and Indigofera gangetica, with various rhizobial strains, showed higher seedling establishment and survival as well as higher biomass than controls (uninoculated treatments) . All legumes established without afterc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…7[link]) and some experimental studies (e.g. Young & Mytton, 1983; Jha et al. , 1995; Parker, 1995) are consistent with the prediction that legumes may sometimes be inferior colonizers due to a scarcity of mutualist partners.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…7[link]) and some experimental studies (e.g. Young & Mytton, 1983; Jha et al. , 1995; Parker, 1995) are consistent with the prediction that legumes may sometimes be inferior colonizers due to a scarcity of mutualist partners.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have demonstrated that rhizobial inoculation can increase various components of plant performance. Examples include the yield of cultivated legumes (Young & Mytton, 1983;Bergersen, 1987;Thies et al, 1991), seedling survival and growth in revegetation projects (Herrera et al, 1993;Jha et al, 1995), and the lifetime reproductive success of Amphicarpaea bracteata (L.) Fernald in a natural habitat in eastern North America not previously occupied by this species (Parker, 1995). A second prediction, from assumptions (1) and (2) together, is that introduced legume populations may occasionally go extinct if inoculated rhizobia fail to survive due to competition from indigenous soil organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Legumes are especially well suited for reestablishing vegetation and stabilizing degraded and metal contaminated soils. This is due to several factors: first, they accumulate nitrogen in a mineralizable form in symbiosis with rhizobia, which then becomes available to non-leguminous plants; second, they are able to grow in low nutrient conditions; and third, they are able to colonize barren habitats which are subject to strong winds and flooding (Jha et al 1995). Jha and co-workers studied how this rhizobial symbiosis influences the ability of several wild legumes to revegetate an unreclaimed limestone quarry.…”
Section: Phytostabilizationmentioning
confidence: 98%
“…Rhizobia are Gram-negative soil bacteria that have economic value and agronomic significance due to their ability to establish a nitrogen-fixing symbiosis with leguminous plants. However, many environmental factors, including heavy and transition metals, often limit the potential of symbiotic systems and have negative effects on both growth and nitrogen fixation of rhizobia (13). Recently, many rhizobial strains with enhanced ability to survive in the presence of high concentrations of heavy and transition metals have been isolated from the root nodules of various legumes (14,15).…”
mentioning
confidence: 99%